Unpacking the Network Processes and Outcomes of Online and Offline Humanitarian Collaboration. (February 2019) - Lai, Chih-Hui; She, Bing; Ye, Xinyue
Employing a bona fide network perspective, this study investigates the network processes and outcomes of organizational collaborative networks before and following Typhoon Haiyan, taking into account the influences of network factors, organizational attributes, and environmental exigencies. The analysis from an online survey with relief organizations and those organizations' Twitter data showed the consistent influence of past relationships on the formation of subsequent relationships after the disaster. In the on-the-ground network, a few highly active organizations stood out and engaging in multiple modes of communication with resource contacts was seen as an adaptive practice that helped organizations to build resource ties after the typhoon. In the online domain, organizations developed post-typhoon networks by means of becoming directly linked to one another and becoming equally resourceful in building their ties. In addition, different forms of resilience were observed as outcomes of collaborative networks. Findings of this study present theoretical and practical implications by unveiling the network dynamics of contemporary humanitarian actions.